Risk of Prediabetes and Diabetes in Oral Lichen Planus: A Case–Control Study according to Current Diagnostic Criteria - Lucía Rodríguez-Fonseca; Santiago Llorente-Pendás; María García-Pola (Diagnostics, 2023)
Objective: To estimate the prevalence of prediabetes and diabetes in patients with oral lichen planus (OLP). Methods: Prospective cohort, including consecutive patients diagnosed clinically and histologically with OLP from 2018 to 2022. Patients and controls were matched by age and gender. Fasting plasma glucose value collection from all patients. Multivariate regression analysis evaluated the relationship between prediabetes and diabetes variables according to current diagnostic criteria. Results: The sample comprised 275 patients (207 women; 75.3%), mean age 59.60 ± 12.18 years for both groups. Prediabetes was diagnosed according to the American Diabetes Association (ADA, 100–125 mg/dL), in 21.45% of OLP patients (59/275) and 14.55% (40/275) of control patients (p = 0.035). Patients with the atrophic-erosive form exhibited stronger association with taking oral antidiabetics (p = 0.011). Multivariate analysis showed that being over >60 years and having a cutaneous location was associated with ≥3 sites (OR 1.81 and OR 2.43). ADA prediabetes and oral antidiabetics drugs increased the probability of OLP (OR 1.60 (1.04–2.51), p = 0.03 and OR 2.20 (1.18–4.69), p = 0.017) after adjustment for sex and age. Conclusions: Because glycemia 100–125 mg/dL was associated with OLP, testing serum fasting plasma glucose seems reasonable in order to prevent development of diabetes and deal with possible complications until new studies are complete.